ANALYSIS OF SOCIO-CULTURAL VALIDITY AND BUSINESS MANAGEMENT IN E-COMMERCE ADOPTION IN FAST FOOD SMEs - Fari Aus; Bunga Kartika; Muh. Husriadi (Adisam Publisher, 2025)
Digital transformation through e-commerce offers opportunity big for fast food SMEs, however​ social cultural resistance and limitations business management becomes an obstacle main in the adoption process. This study aims to analyze socio-cultural validity and readiness management in adopting e-commerce in fast food SMEs, as well as identify factors key influencing​ success digital transformation. The research method uses a qualitative approach with case studies, involving interview in-depth and observation participatory in MSME actors in urban areas. The results of the study revealed that the value family and interaction look at advance Still dominant, causing resistance to digital transactions, while limitations capacity managerial and digitalization of internal processes hinders e-commerce optimization. This finding confirms the need integration of cultural approaches and strengthening organizational capabilities to support technology adoption effective. Implications the practical thing is the importance ongoing training and contextual mentoring, as well as support policies that are adaptive to characteristics local fast food MSMEs. This study contributes to the development of a more inclusive and sustainable e-commerce adoption model in the culinary MSME sector.